Dysphagia and Dysphonia in a case of Miller Fisher Syndrome: Speech therapy evaluation - Marcelino, Arthur Brito (2022)
The case report of a male patient admitted to the emergency hospital with the diagnosis of Miller Fisher syndrome (MF), is presented. MFS is characterized by the presence of a triad of signs: ophthalmoparesis, areflexia and ataxia, and may present other less frequent signs such as speech and swallowing disorders. On the basis of findings during the speech therapy evaluation it was possible to identify severe oropharyngeal dysphagia, vocal hypernasality and other speech disorders. The patient presented a good evolution following an integrated multi-professional treatment program, including speech-language therapy.